Peningkatan Kemampuan Teknik Dasar Lempar Lembing Melalui Metode Visual Dengan Pendekatan Berdiferensiasi - Raehan, A. Muh.; Hudain, Muh. Adnan; Muhammadong, Muhammadong; Arimbi, Arimbi; Juhanis, Juhanis (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This study aims to improve the basic javelin throwing technique skills of grade VIII students of MTS Al-Huda' Mannaungi Bulukumba Regency through the application of visual methods with a differentiated approach. This research was conducted to overcome the problems of students who face obstacles in mastering the basic javelin throwing technique, including how to grasp the javelin, body position when throwing, and the correct javelin release technique. This study uses the Classroom Action Research (PTK) method with the Kemmis and McTaggart models which consists of four stages: planning, action, observation, and reflection. The subjects of the study were 30 students of grade VIII of MTS Al-Huda' Mannaungi, Bulukumba Regency. The research was conducted in two cycles, with each cycle lasting two weeks in March 2025. The assessment instrument covers 10 psychomotor aspects with a total score of 100, and the Minimum Completeness Criteria (KKM) is set at a score of 75. The results showed a significant improvement in students' javelin throwing basic technique skills. In the pre-cycle, only 5 students (17%) achieved KKM with an average score of 65.66. After the first cycle, the number of students who completed increased to 15 students (50%) with an average score of 71.33. In cycle II, there was a very significant increase with 28 students (93%) declared complete and the average score reached 77.26. The highest score achieved is 88, while the lowest score is 65. The visual method with a differentiated approach has proven to be very effective in improving students' basic javelin throwing skills. The increase in classroom learning completeness reached above 80% with an average score of 77.26 which exceeded the predetermined KKM. The combination of visual methods and differentiated approaches provides a more comprehensive learning experience, allowing students to learn according to their respective needs, abilities, and learning styles, making learning more meaningful and effective.